The Role of Human Agency in Global Urban Health - Kai Michael Gensitz; Catherine Woods; Tadhg MacIntyre; Claudio R. Nigg (Current Issues in Sport Science)
Introduction Global health is facing critical challenges (e.g., climate change, environmental degradation, biodiversity loss, increasing non-communicable diseases), particularly within urban settings (e.g., cities) where over half of the global population resides (Romanello et al., 2024). As rapid urbanization continues, pressures of current global health challenges increasingly threaten both human and nature health. Drawing upon previous health concepts (e.g., Global Health, Planetary Health, Biodiversity-Health-Nexus), this research postulates a new multi-dimensional approach to health indicators. This research emphasises human agency (i.e., ability of individuals to make choices and take action; Bandura, 2006) as core tenet and – grounded in a socio-ecological perspective (see Hagger, 2024) – both the recent driver of and the potential solution to global health challenges within urban settings, resulting in a novel concept of Global Urban Health.